Feel well and do well at work: A post-relocation study on the relationships between employee wellbeing and office landscape. Issue 2 (7th June 2019) - Cobaleda Cordero, Antonio; Babapour, Maral; Karlsson, MariAnne
Abstract : Purpose: This paper aims to investigate employee well-being in relation to office landscapes in a post-relocation context. The aims are to identify spatial attributes of the office landscape that influence employee well-being and underlying contextual factors that explain employee well-being post-relocation. Design/methodology/approach: A mixed-method approach was adopted. The data collection involved 16 semi-structured interviews with employees, an interview with the leading architect of the office renovation, study of a dossier on the renovation project and observations. Findings: Most of the informants experienced the new office landscape positively despite few shortcomings. Spatial attributes were identified that influenced the informants' well-being positively in terms of affects, satisfaction, social relations and environmental mastery. Conversely, negative influences on well-being were also reported regarding affects, satisfaction and environmental mastery. Conflicting views on some of the spatial attributes and contextual factors related to the planning process and the former office landscape were identified. Originality/value: The value of this paper lies in investigating the office landscape at the spatial attributes level, despite office type, and their influence on hedonic and eudaimonic components of employee well-being. The research approach adopted proved its usefulness for in-depth studies of the interrelations between office landscapes and employee well-being.